(untitled) (Communications in Inorganic Synthesis, 2018)
The history of a unique stable and soluble complex Pd2(dba)3 has been considered starting with the classical oxidative addition and finishing by the modern synthesis of Pd nanoclusters catalysts absorbed on the carbon and non-carbon polymer supports. Coordinatively non-saturated Pd(0) particles are used for constructing nanopalladium clusters immobilised which are active as catalysts in the cross-coupling reactions.